2014
DOI: 10.1016/j.ydbio.2014.06.012
|View full text |Cite
|
Sign up to set email alerts
|

Arx together with FoxA2, regulates Shh floor plate expression

Abstract: Mutations in the Aristaless related homeodomain transcription factor (ARX) are associated with a diverse set of X-linked mental retardation and epilepsy syndromes in humans. Although most studies have been focused on its function in the forebrain, ARX is also expressed in other regions of the developing nervous system including the floor plate (FP) of the spinal cord where its function is incompletely understood. To investigate the role of Arx in the FP, we performed gain-of-function studies in the chick using… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
36
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 28 publications
(37 citation statements)
references
References 61 publications
1
36
0
Order By: Relevance
“…One day after IUEP, the dams were sacrificed and the brains were removed. The E13.5 embryonic brains were fixed overnight in 4% paraformaldehyde and prepared for cryosectioning (15 μm) as described [7]. All sections were imaged using Zeiss Zen Pro software driving a Hamamatsu ORCA-Flash 4.0 camera attached to a Zeiss Observer Z1 inverted microscope (Carl Zeiss, Oberkochen, Germany).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…One day after IUEP, the dams were sacrificed and the brains were removed. The E13.5 embryonic brains were fixed overnight in 4% paraformaldehyde and prepared for cryosectioning (15 μm) as described [7]. All sections were imaged using Zeiss Zen Pro software driving a Hamamatsu ORCA-Flash 4.0 camera attached to a Zeiss Observer Z1 inverted microscope (Carl Zeiss, Oberkochen, Germany).…”
Section: Methodsmentioning
confidence: 99%
“…Briefly, primers were designed using Agilent QuikChange Primer Design software and PCR was performed by KOD Xtreme ™ Hot Start DNA Polymerase (Novagen) using pCAG-Arx-IRES-GFP as a template [7]. The PCR products were digested with DpnI (NEB) and transformed into DH10B E .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Arx is expressed in several areas of the nervous system, and in the floorplate Arx together with FoxA2, directly induces Sonic hedgehog (Shh) expression through binding to an Shh floor plate enhancer (SFPE2) [137]. Nkx2.2, induced by Shh, then down-regulates Arx expression, showing hence a regulatory loop during vertebrate development.…”
Section: 213b Animal Models and Functional Studiesmentioning
confidence: 99%
“…Several genetic models showed that this pathway is important for proper neural tube closure and disruption of Shh signaling leads to NTDs (Murdoch and Copp, 2010). In mice, Foxa2 mediates Shh signaling in the floor plate, a critical organizing center for neural tube patterning (Cho et al, 2014; Mansour et al, 2011). Given the poised state of putative FOXA2 enhancers and that the gene is not expressed in NRs (TPM < 1), it may be possible that this gene is activated at a later stage of NT development.…”
Section: Resultsmentioning
confidence: 99%